An X‐ray Raman spectrometer for EXAFS studies on minerals: bent Laue spectrometer with 20 keV X‐rays. (8th February 2013) - Hiraoka, N.; Fukui, H.; Tanida, H.; Toyokawa, H.; Cai, Y. Q.; Tsuei, K. D.
<x xml:space="preserve">Abstract</x> An X‐ray Raman spectrometer for studies of local structures in minerals is discussed. Contrary to widely adopted back‐scattering spectrometers using ≤10 keV X‐rays, a spectrometer utilizing ∼20 keV X‐rays and a bent Laue analyzer is proposed. The 20 keV photons penetrate mineral samples much more deeply than 10 keV photons, so that high intensity is obtained owing to an enhancement of the scattering volume. Furthermore, a bent Laue analyzer provides a wide band‐pass and a high reflectivity, leading to a much enhanced integrated intensity. A prototype spectrometer has been constructed and performance tests carried out. The oxygen K‐edge in SiO2 glass and crystal (α‐quartz) has been measured with energy resolutions of 4 eV (EXAFS mode) and 1.3 eV (XANES mode). Unlike methods previously adopted, it is proposed to determine the pre‐edge curve based on a theoretical Compton profile and a Monte Carlo multiple‐scattering simulation before extracting EXAFS features. It is shown that the obtained EXAFS features are reproduced fairly well by a cluster model with a minimal set of fitting parameters. The spectrometer and the data processing proposed here are readily applicable to high‐pressure studies.